Looking after bubba for all our mob: Aboriginal and Torres Strait Islander community experiences and perceptions of stillbirth - Massi, Luciana; Lewis, Carolyn; Stewart, Skye; Jans, Diana; Gautam, Rupesh; Jalloub, Lina; Bowman, Anneka; Middleton, Philippa; Vlack, Sue; Boyle, Frances M.; Shepherd, Carrington; Flenady, Vicki; et al. (Frontiers in Public Health, 2024)
The stillbirth rate among Aboriginal and Torres Strait Islander women and communities in Australia is around double that of non-Indigenous women. While the development of effective prevention strategies during pregnancy and improving care following stillbirth for women and families in communities has become a national priority, there has been limited progress in stillbirth disparities. With community permission, this study aimed to gain a better understanding of community experiences, perceptions, and priorities around stillbirth. We undertook an Indigenous researcher-led, qualitative study, with community consultations guided by a cultural protection protocol and within an unstructured research framework. A total of 18 communities were consulted face-to-face through yarning interviews, focus groups and workshops. This included 54 community member and 159 health professional participants across remote, regional, and urban areas of Queensland, Western Australia, Victoria, South Australia, and Northern Territory. Thematic analysis of consultation data identified common themes across five focus/priority areas to address stillbirth: Stillbirth or Sorry Business Baby care needs to be family-centered; using Indigenous “ways of knowing, being, and doing” to ensure cultural safety; application of Birthing on Country principles to maternal and perinatal care; and yarning approaches to improve communication and learning or education. The results underscore the critical need to co-design evidence-based, culturally appropriate, and community-acceptable resources to help reduce existing disparities in stillbirth rates.